1986
DOI: 10.1017/s0021859600069653
|View full text |Cite
|
Sign up to set email alerts
|

Growth, tissue deposition and metabolism studies in growing pigs given low glucosinolate rapeseed meal diets containing different amounts of copper and polyethylene glycol

Abstract: In three factorial growth experiments and a metabolism experiment pigs of approximately 25 kg initial live weight were given on a restricted scale of feeding simple diets, based on barley, a vitamin and mineral supplement and either soya-bean meal (SBM) or a low glucosinolate rapeseed meal (cv. Tower; TRSM). Variations in these two basic diets were produced by adding different quantities of tannic acid, polyethylene glycol (PEG) and copper (Cu).Diets based on soya-bean meal were used in the first experiment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The considerable increase in rapeseed meal intake and in growth rate resulting from supplementation with both iodine and copper at a level of 315 mg/kg DM, agrees with the results of Ludke, Sch6ne and Hennig (1985) The favorable effects of copper may result from modifications or suppression of the gut microflora (Braude, 1965) ― consequently, the production of toxic compounds from glucosinolates could be reduced (Rowan and Lawrence, 1986) ― or from the formation of stable complexes with progoitrin, limiting the formation of goitrin (Cansfield and Campbell, 1980) which would explain its antigoitrogenic effects. In addition, Ludke, Sch6ne and Hennig (1985) showed in vitro that the addition of copper sulphate solutions to rapeseed meal reduced ITC and VTO formation, perhaps as a result of stable linkages with glucosinolates.…”
supporting
confidence: 85%
“…The considerable increase in rapeseed meal intake and in growth rate resulting from supplementation with both iodine and copper at a level of 315 mg/kg DM, agrees with the results of Ludke, Sch6ne and Hennig (1985) The favorable effects of copper may result from modifications or suppression of the gut microflora (Braude, 1965) ― consequently, the production of toxic compounds from glucosinolates could be reduced (Rowan and Lawrence, 1986) ― or from the formation of stable complexes with progoitrin, limiting the formation of goitrin (Cansfield and Campbell, 1980) which would explain its antigoitrogenic effects. In addition, Ludke, Sch6ne and Hennig (1985) showed in vitro that the addition of copper sulphate solutions to rapeseed meal reduced ITC and VTO formation, perhaps as a result of stable linkages with glucosinolates.…”
supporting
confidence: 85%
“…The information on effects of PEG supplementation on the performance of pigs fed leaf mealcontaining diets is scarcely documented. Rowan & Lawrence (1986) studied growth, tissue deposition, and metabolism from growing pigs fed on rapeseed meal treated with different levels of PEG and copper, and they determined that PEG at 17 g/kg DM significantly improved growth rate. Savage et al (1980) reported the positive influence of micronization and polyethylene glycol on the nutritional value of brown sorghum for growing pigs.…”
Section: Performance Of Pigs Fed Leguminous Leaf Meal Treated With Polyethylene Glycolmentioning
confidence: 99%